Ղարաբադյան հակամարտությունը որպես տեղեկատվական պատերազմի տարատեսակ - Կրիստինա Գասպարյան (ՀՀ ԳԱԱ հրատ.)
The conflict o f Karabakh was a chaHenge (and continues to be one) not only for Armenian soldiery and politicians, but also for mass media. If until recently wars were held mostly in the informational field, now reverse connection, both on macro and micro levels is noticed. Journalists, together with PR specialists,have long ago become the third force of any conflict, and in connection with on what side do they play stronger that attains the victory.
Keywords: Journalism; The periodical Press, etc.; Modern History; Language and Literature